Sarau poético: caminhos para uma experiência teatral - Xavier, Rosa Samara Silveira (2018)
The present study gathers reflections on the students' experience with the practice of a theatrical project in highschool of the Picuí campus, in the Federal Institute of Education, Science and Technology - IFPB. The term experience must be different, not easy to define, because its meaning is tied to its context, being modified according to the objectives and times. In the current study, it is related to the individual's experiences and the way in which he relates to the environment, with himself, with others and with objects, being able to transform himself and transform what he relates to, as Dewey (2010) points out. On the other hand, it suggests alterity, if put in another place or in someone else's position, being allowed to be touched according to Bondía (2002).It is considered here the proposal of a poetry slam as a means of engaging the students during the path of creation that is accomplished from the reading of poems for the construction of a theatrical composition. This research evidences the importance of the students' experience with the specifics of a creative process in the theater, but also discusses the issues of theater teaching from the perspective of the teacher of the Art discipline in the context of the IFPB to act as a polyvalent teacher of the area, causing various practical difficulties, de-characterizing the specificities of artistic languages.These ideas are based on the understanding of the educational field in which the project is inserted, the concept of experience, together with studies on theater plays and improvisation in pedagogical practices and the understanding of the creative process in art. The pedagogical practices of the author as a teacher at this institution were sources of field observation, with investigations in classroom applications and interviews with students involved in the research process. It can be seen that these practices contribute to students' self-knowledge, as well as the possibility of promoting theater teaching for secondary school students together with possible reverberations in the institutional environment.